First-morning urine osmolality changes in children with nocturnal enuresis at the end of treatment - Yun Ha Lee; Jae Min Chung; Sang Don Lee (Korean Society of Pediatric Nephrology, 2024)
Purpose The ability to concentrate urine becomes an important index in determining nocturnal enuresis (NE) treatment. The aim of our study was to investigate first-morning urine osmolality (Uosm) changes at the end of treatment compared to before treatment in children with NE. Methods A total of 71 children with NE were divided into two groups according to the level of first-morning Uosm before treatment: high group (≥800 mOsm/kg) and low group (<800 mOsm/kg). Baseline parameters were obtained from uroflowmetry, frequency volume charts for at least 2 days, and a questionnaire for lower urinary tract symptoms. All patients were basically treated with standard urotherapy and medication. The first-morning Uosm was measured twice, before treatment and at the end of treatment. Results The response rate was higher in the low group after 3 months of treatment than in the high group (P=0.041). However, there was no difference between the two groups at the end of the treatment. In the high group, the first-morning Uosm at the end of treatment did not show a significant change compared to before treatment. In contrast, the first-morning Uosm increased in the low group at the end of treatment (P<0.001). However, it was still lower than that of the high group (P=0.007). Conclusions The ability to concentrate nocturnal urine improved at the end of treatment compared to before treatment in the low Uosm NE children. In addition, NE improved faster in the low Uosm group before treatment than in the high group.